Thermodynamics of second-grade nanofluid over a stretchable rotating porous disk subject to Hall current and cubic autocatalysis chemical reactions - Khan, Noor Saeed; Fernandez-Gamiz, Unai; Khan, Muhammad Sohail; Kumam, Wiyada; Kumam, Poom; Galal, Ahmed M. (Frontiers in Physics, 2022)
Homogeneous-heterogeneous chemical reaction for second-grade nanofluid and gyrotactic microorganisms in a rotating system with the effects of magnetic field and thermal radiation is examined. The boundary layer equations of the problem in non-dimensional form are evaluated by a strong technique namely homotopy analysis method (HAM). The rates of flow, heat, mass and gyrotactic microorganisms motion are obtained for the augmentations in the pertinent parameters. The graphical pictures of the results are described by the physical significance. The Hall current effect decreases the azimuthal velocity, axial velocity increases with the injection of mass, Biot number leads to the enhanced heat transfer, gyrotactic microorganisms concentration diffusion rate decreases with Peclet number and concentration of chemical reaction is reduced with Schmidt number. Excellent agreement of the present work is found with the previously published work. The present study has applications in the hydromagnetic lubrication, semiconductor crystal growth control, austrophysical plasmas, magnetic storage disks, computer storage devices, care and maintenance of turbine engines, aeronautical, mechanical and architectural engineering, metallurgy, polymer industry, hydromagnetic flows in porous media, food processing and preservation process.